Upaya Pencegahan Radikalisme Berbasis Lokalitas Madura Pada Mata Kuliah Pendidikan Agama Islam Di Perguruan Tinggi Negeri (Studi Pada Universitas Trunojoyo Madura) - Mukhlishah AM (Proceedings of Annual Conference on Islamic Educational Management, 2021)
This research is an effort to find out the radicalism movement in state universities and prevention efforts through the process of Islamic religious education at Trunojoyo University, Madura. The research approach method is phenomenology-ethnographic. While based on the scientific field, this research includes education and socio-religious research, namely academic studies of education, social religion and religion. Methods of data collection, by means of observation, interviews, and a series of identification processes. The results showed that First, the learning process of Islamic Religious Education at Trunojoyo University, Madura, was carried out as the coordinator of the General Course, at the Islamic Faculty. In the learning process, in addition to conducting face-to-face meetings in the classroom, there is also an obligation for students to take part in mentoring activities that are carried out outside the classroom, which are used as reinforcement of religious character education for students. Second, the characteristics of the radicalism movement have generally started to grow and have a strong basis among students, and some lecturers. In the framework of further prevention, in the learning process of Islamic Religious Education, including through the counter radicalization movement, namely by approaching and internalizing. As in the matter of how to embody Islam in Indonesia, students are required to analyze how Islamic teachings in the context of modernity and Indonesian-ness by presenting the results of work projects on how to implement Islamic teachings. The second way, including the process of deradicalization, including the efforts built among them are how both lecturers and mentees to spread the moderation aspects adopted, as well as through psychological approaches, both arising from students and from lecturers / education personnel